Exergy analysis on the process with integrated supercritical water gasification of coal and syngas separation. (5th January 2018) - Chen, Zhewen; Zhang, Xiaosong; Han, Wei; Gao, Lin; Li, Sheng
Highlights: Exergy analysis of a process with supercritical water gasification of coal is conducted. The exergy conversion mechanism of the process is obtained. The exergy destruction and distribution of the process is analyzed. A maximum exergy efficiency of 89.18% is obtained. Abstract: Supercritical water gasification (SCWG) is a promising technology for clean and efficient coal utilization. The exergy analyses on the processes with integrated SCWG of coal and syngas separation are conducted for clear understanding about the exergy distributions in the processes. The energy level of the heat provided for the gasifier is upgraded to the energy level of the syngas, which is driven by the decrease of energy levels from the coal to the syngas. The minimum temperatures of the heat provided for the gasifier are obtained in different coal-water-slurry concentrations (CWSCs). The total exergy destruction firstly increases, and then decreases with increasing CWSC. The maximum total exergy destruction of the process is obtained when the CWSC is approximately 10%. The exergy efficiency of the process has a converse trend with the total exergy destruction. When the CWSC is in the range of 6% and 20%, the maximum exergy efficiency is 89.18%. The origins for the production of the exergy destruction are also studied.